Photoluminescence Studies of In0.5Ga0.5As/GaAs quantum dots - Wahab, Yussof; Yeong, Wai Woon; Deraman, Karim; Soh, Chew Beng; Muhammad, Rosnita (2006)
In this paper, we present an experiment study of the photoluminescence properties of self-assembled In0.5sGa0.5As/GaAs quantum dots (aDs). High quality In0.5Ga0.5As aDs were grown by using Metalorganic Chemical Vapor Deposition (MOCVD). The low temperature photoluminescence (PL) spectrum of the Ino.sGao:As quantum dots surrounded by GaAs exhibit an emission peak at 1.137 to 1.182eV and a narrow linewidth (FWHM). The PL peak energy and intensity are varied with the excitation powers. Room temperature PL shows slightly lower peak energy with a broader spectrum linewidth. The distribution of the peak energy, peak intensity, and FWHM for the whole sample was obtained by using the PL mapping method.